Evolution of Research on Religion–State Relations in Constitutional Law Using Biblioshiny Network Visualization Analysis - Saputra, Amri; Alim, Ansorul; Ricardo, David; Bin Suparti, Shukri (Yayasan Cahaya Generasi Positif, 2025)
This research aims to analyze the evolution of scholarly literature concerning the relationship between religion and state within the context of constitutional law through a comprehensive bibliometric approach. The research data were collected from the Scopus database spanning the period from 2005 to 2025 and were analyzed using the Biblioshiny for R software. The analysis process involved various visualizations, such as annual scientific production, average citation per year, three-field plot, most relevant words, affiliations, treemap, and a thematic map. The findings indicate that publications on this topic have experienced a significant upward trend, although fluctuating, with a peak observed in 2023. Thematically, constitutional law, religion, and human rights emerged as motor themes that drive the direction of research development, while Islamic law, democracy, and legal pluralism served as basic themes forming the conceptual foundation. Furthermore, the affiliation analysis reveals that the primary contribution originates from international institutions, whereas the participation of researchers from Indonesia remains limited but shows a positive upward trend. These findings underscore the importance of strengthening local and contextual perspectives within the global discourse to enrich the understanding and development of constitutional law studies that are more inclusive and relevant to contemporary sociopolitical dynamics.